Frustrated charge density wave and quasi-long-range bond-orientational order in the magnetic kagome FeGe - D. Subires; A. Kar; A. Korshunov; C. A. Fuller; Yi Jiang; H. Hu; D. Călugăru; C. McMonagle; C. Yi; S. Roychowdhury; W. Schnelle; C. Shekhar; et al. (Nature Communications)
Abstract The intrinsic frustrated nature of a kagome lattice is amenable to the realization of exotic phases of matter, such as quantum spin liquids or spin ices, and the multiple-q charge density waves (CDW) in the kagome metals. Despite intense efforts to understand the mechanism driving the electronic modulations, its origin is still unknown and obscured by competing interactions and intertwined orders. Here, we identify a dimerization-driven 2D hexagonal charge-diffuse precursor in the antiferromagnetic kagome metal FeGe and demonstrate that the fraction of dimerized/undimerized states is the relevant order parameter of the multiple-q CDW of a continuous phase transition. The pretransitional charge fluctuations with propagation vector q = q M at TCDW < T < T*(125 K) are anisotropic, hence holding a quasi-long-range bond-orientational order. The broken translational symmetry emerges from the anisotropic diffuse precursor, akin to the Ising scenario of antiferromagnetic triangular lattices. The temperature and momentum dependence of the critical scattering show parallels to the stacked hexatic B-phases reported in liquid crystals and transient states of CDWs and highlight the key role of the topological defect-mediated melting of the CDW in FeGe.